ANALISIS PERBANDINGAN HASIL TANGKAPAN IKAN CAKALANG (Katsuwonus pelamis) SEBELUM DAN SAAT MASA PANDEMIC COVID-19 DI KABUPATEN SORONG: Studi Kasus Di PT. Radios Apirja Sorong - Yosua Naa; Dwi Indah Widaya Yanti; Clara Payung; Melisa Masengi; Roger R. Tabalessy (INTEGRATED OF FISHERIES SCIENCE, 2023)
Pole and line in the waters of Sorong have contributed significantly to the level of fishery production in West Papua. Based on data from the related service, the production of catches is quite large and there is an increase from year to year. Catching fish using pole and line fishing gear by looking for schools of surface fish that cluster in large enough numbers. The purpose of this study was to determine the comparison of catches before and during the covid 19 pandemic to the catches of Pole and Line vessels at PT. Radios Apirja Sorong and to find out the impact of Pole and Line crew income before and during the covid-19 pandemic The average catch of pole and line vessels at PT. Radios Apirja Sorong before the COVID-19 pandemic (2019) was 77.57 tons per month while the average catch during COVID-19 (2020) was 69.78 tons per month, so the average pole and line boat catch before COVID -19 can be said to be still good, but during the COVID-19 pandemic the average catch decreased (minus) by 7.79 tons per month.